The Effect of The "Judges' Pens" Strategy on Chemistry Achievement Among First Intermediate Grade Students (Journal of the College of Basic Education, 2026)
The present study aims to investigate the effect of the "Judges' Pens" strategy on chemistry achievement of first intermediate grade students in chemistry. The researchers adopted a partially controlled experimental design. The research population consisted of first-intermediate-grade students in intermediate and secondary schools. Al-Intifada Al-Sha'baniyah Intermediate School was intentionally selected, and one class was randomly assigned as the experimental group, consisting of (30) students who were taught using the Judges' Pens strategy. Another class was assigned as the control group, consisting of (30) students who were taught using the conventional method. Thus, the total sample comprised (60) students. The two groups were equated based on several variables, including chronological age (in months), a prior knowledge test, previous achievement in science, and an intelligence test. The instructional content was limited to the first and second chapters of the chemistry textbook prescribed for first intermediate grade students for the academic year (2025–2026). A total of (118) behavioral objectives were formulated for these two chapters, and (24) lesson plans were prepared for each of the experimental and control groups. The researcher taught both groups (experimental and control). As for the research instrument, an achievement test was constructed, consisting of (40) objective multiple-choice items. The data were analyzed using the Statistical Package for the Social Sciences (SPSS).The results showed that students in the experimental group outperformed those in the control group on the achievement test. Considering these findings, the researchers presented several recommendations and suggestions.